A polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film and its preparation method and application
By uniformly dispersing and oriented arrangement of polydopamine-modified boron nitride nanosheets in the polyimide matrix, the problems of interface pores and interface thermal resistance between boron nitride nanosheets and polyimide films in the prior art are solved. Significantly improves thermal conductivity and maintains good breakdown strength.
Patent Information
- Application Number
- CN202210569726.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-05-24
AI Technical Summary
The thermal conductivity of existing polyimide thermal composite materials is affected by the interface pores and interface thermal resistance between boron nitride nanosheets and polyimide films, resulting in poor thermal conductivity.
By combining polydopamine-modified boron nitride nanosheets with polyimide matrix, and using electrospinning and molding and other processes, the uniform dispersion and orientation of boron nitride nanosheets in the polyimide matrix are achieved. Reduce interface defects and heat transfer resistance.
The thermal conductivity coefficient of the polydopamine-modified boron nitride nanosheet/polyimide thermal composite film is significantly improved, and good breakdown strength is maintained, extending the service life of the film.
Smart Images

Figure CN114750491B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of polymer-based composite films, and relates to a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film and a preparation method and application thereof. Background Art
[0002] Polyimide (PI) is a polymer material with excellent comprehensive performance. It has many advantages such as excellent high and low temperature resistance, good chemical corrosion resistance, outstanding electrical insulation and high dimensional stability. It has been widely used in aviation, aerospace and microelectronics. However, PI itself has poor thermal conductivity and poor dispersion of thermal conductive fillers in the PI matrix. Therefore, it is particularly important to improve the thermal conductivity and insulation properties of PI-based composite films.
[0003] At present, most of the PI thermal conductive composite materials are prepared by filling a single high thermal conductivity and low dielectric inorganic filler. Boron nitride nanosheets (BNNS) have many advantages, such as high thermal conductivity (λ), low dielectric constant (ε) and dielectric loss tangent (tanδ), excellent oxidation resistance and corrosion resistance, making them an ideal filler for preparing PI thermal conductive insulating composite materials. However, when BNNS is compounded with PI film, there are pores between the interfaces of the two, and a large interfacial thermal resistance will be generated when blending, thus affecting the transmission efficiency of phonons. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a polydopamine modified boron nitride nanosheet / polyimide thermal conductive insulating composite film and a preparation method and application thereof, thereby obtaining a boron nitride / polyimide thermal conductive composite film with good thermal conductivity.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film comprises the following steps:
[0007] S1: adding polydopamine-modified boron nitride nanosheets into a polyamic acid solution, stirring and reacting, to prepare a dopamine-modified boron nitride nanosheet / polyamic acid solution;
[0008] S2: preparing a polydopamine-modified boron nitride nanosheet / polyamic acid composite fiber felt using the polydopamine-modified boron nitride nanosheet / polyamic acid solution;
[0009] S3: subjecting the polydopamine-modified boron nitride nanosheet / polyamic acid composite fiber felt to thermal imidization treatment to obtain a dopamine-modified boron nitride nanosheet / polyimide thermally conductive composite fiber felt;
[0010] S4: molding several layers of the polydopamine modified boron nitride nanosheets / polyimide thermal conductive composite fiber felt to obtain the polydopamine modified boron nitride nanosheets / polyimide thermal conductive insulating composite film.
[0011] Preferably, the synthesis process of the polydopamine modified boron nitride nanosheets is specifically as follows: adding tris(hydroxymethyl)aminomethane to a mixed solution of deionized water and ethanol, stirring to fully dissolve the tris(hydroxymethyl)aminomethane, adding boron nitride nanosheets, stirring to evenly disperse the boron nitride nanosheets, then adding dopamine, stirring until the reaction is complete, and obtaining the polydopamine modified boron nitride nanosheets.
[0012] Preferably, before adding the polydopamine-modified boron nitride nanosheets to the polyamic acid solution, the prepared polydopamine-modified boron nitride nanosheets are dried at 60 to 80° C. for 12 to 24 hours to obtain dopamine-modified boron nitride nanosheet powder, and the dopamine-modified boron nitride nanosheet powder is added to the polyamic acid solution.
[0013] Preferably, the synthesis process of the polyamic acid solution is as follows: under ice-water bath conditions, 4,4'-diaminodiphenyl ether is added to N,N-dimethylformamide solution, stirred to completely dissolve 4,4'-diaminodiphenyl ether, and pyromellitic anhydride is added, and stirred continuously until the polymerization reaction is complete to obtain a polyamic acid solution.
[0014] Preferably, during the synthesis of the polyamic acid solution, pyromellitic anhydride is added in several batches; after each addition of pyromellitic anhydride, it is stirred to dissolve and react completely before adding the next batch of pyromellitic anhydride; the weight of each batch of pyromellitic anhydride added does not exceed 0.2 g.
[0015] Preferably, in step S2, the polydopamine-modified boron nitride nanosheet / polyamic acid solution is made into a polydopamine-modified boron nitride nanosheet / polyamic acid composite fiber felt by an electrospinning method; and the voltage of the high-voltage power supply during the electrospinning process is 15 kV to 25 kV.
[0016] Preferably, before subjecting the polydopamine-modified boron nitride nanosheets / polyamic acid composite fiber felt to thermal imidization treatment, the polydopamine-modified boron nitride nanosheets / polyamic acid composite fiber felt is treated under vacuum; the vacuum treatment conditions are: vacuum degree 0.08-0.1 MPa, temperature 60-80°C, time 4-6 hours.
[0017] Preferably, the compression molding temperature is 290-320° C., the pressure is 5-10 MPa, and the time is 10-15 min.
[0018] A polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film is prepared by the above method. The polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film has a thermal conductivity of 0.23-1.75 W / mK and a breakdown strength of 11.8-16.4 kV / mm.
[0019] The polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film prepared by the above method is applied in the field of electronic packaging.
[0020] Compared with the prior art, the present invention has the following beneficial technical effects:
[0021] A preparation method of a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film, using polydopamine-modified boron nitride nanosheets as inorganic fillers, effectively improving the dispersibility of boron nitride nanosheets, increasing the contact area between thermally conductive fillers and thermally conductive fillers, and between thermally conductive fillers and fibers, reducing interface defects and heat transfer resistance between the matrix and fillers, reducing the scattering of phonons during the diffusion process, and thus improving the thermal conductivity of the composite material. A method combining in-situ polymerization, electrostatic spinning and compression molding is adopted to achieve uniform dispersion and directional arrangement of polydopamine-modified boron nitride nanosheets inside the polyimide matrix, so that the thermal conductivity of the polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film is significantly improved, and at the same time, due to the strong viscosity of polydopamine, the composite film maintains good breakdown strength.
[0022] Furthermore, the polydopamine-modified boron nitride nanosheets are added to the polyamic acid solution in the form of dry powder, which effectively improves the dispersibility of the polydopamine-modified boron nitride nanosheets in the polyamic acid solution. Generally, the polydopamine-modified boron nitride nanosheets are dispersed in water, and the polyamic acid solution is easily polymerized and precipitated in water. If the aqueous dispersion of the polydopamine-modified boron nitride nanosheets is mixed with the polyamic acid solution, the polyamic acid will precipitate, reducing the yield of the target product.
[0023] Furthermore, during the synthesis of the polyamic acid solution, adding pyromellitic anhydride in batches can effectively reduce the heat generated during the dissolution of pyromellitic anhydride, avoid the self-polymerization process of pyromellitic anhydride, reduce the occurrence of side reactions, and improve the yield of the target product.
[0024] Furthermore, the electrospun nanofiber membrane prepared by electrospinning has high porosity, good interconnectivity, micron-level gaps and a large surface-to-volume ratio, making it an excellent material for thermal conductivity of electronic components; the polydopamine-modified boron nitride nanosheets / polyamic acid solution is made into a polydopamine-modified boron nitride nanosheet / polyamic acid composite fiber felt by the electrospinning method, which can effectively improve the uniformity of the distribution of thermal conductive fillers in the fiber and improve the thermal conductivity of the material.
[0025] Furthermore, vacuum treatment is used to remove N,N-dimethylformamide (DMF) from the polydopamine-modified boron nitride nanosheets / polyamic acid composite fiber felt. This method has high removal efficiency and avoids the volatilization of organic solvents into the room. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 Flow chart of preparing BNNS@PDA / PI composite film of the present invention;
[0028] Figure 2 The thermal conductivity test results of the BNNS@PDA / PI composite films prepared in Examples 1 to 4 of the present invention;
[0029] Figure 3 The comparison results of thermal conductivity of BNNS@PDA / PI composite films prepared in Comparative Examples 1-2 and Examples 1-2 of the present invention;
[0030] Figure 4 The comparison results of the breakdown strength of the BNNS@PDA / PI composite films and the pure PI films prepared in Comparative Examples 1-2 and Examples 1-2 of the present invention are shown. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0032] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0033] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0034] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0035] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0036] The present invention provides a method for preparing a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film, using polyamic acid (PAA) obtained by polycondensation of 4,4'-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) as a matrix, polydopamine-modified boron nitride nanosheets (BNNS@PDA) as a thermally conductive insulating filler, and using an electrostatic spinning method to prepare a polydopamine-modified boron nitride nanosheet / polyamic acid (BNNS@PDA / PAA) thermally conductive insulating composite fiber felt, and then using a thermal imidization and compression molding process to prepare a polydopamine-modified boron nitride nanosheet / polyimide (BNNS@PDA / PI) thermally conductive insulating composite film with high thermal conductivity and low dielectric constant. Specifically, Figure 1 As shown, a method for preparing a polydopamine modified boron nitride nanosheet / polyimide thermal conductive insulating composite film comprises the following steps:
[0037] S1: Preparation of polydopamine modified boron nitride nanosheets (BNNS@PDA): Tris (hydroxymethylaminomethane) was added to a mixed solution of deionized water and ethanol in a volume ratio of 3:1, and Tris was stirred to fully dissolve. Boron nitride nanosheets (BNNS) were added, and the mixture was dispersed evenly after ultrasonic treatment. BNNS was dispersed evenly after stirring, and ultrasonic treatment was also performed to assist the dispersion of BNNS. Dopamine (DA) was then added and stirred until the reaction was complete. At this time, the solution was gray-black. After standing at room temperature, the supernatant was removed, and the precipitated product was dried at 60-80°C for 12-24h to obtain polydopamine modified boron nitride nanosheets (BNNS@PDA).
[0038] Preparation of polyamic acid (PAA) solution: Add 4,4'-diaminodiphenyl ether (ODA) to N,N-dimethylformamide (DMF) solution under ice-water bath conditions, stir to completely dissolve 4,4'-diaminodiphenyl ether (ODA), add pyromellitic anhydride (PMDA) in several batches, stir to dissolve and react completely after each addition of PMDA, and then add the next batch of PMDA. The weight of PMDA added in each batch does not exceed 0.2g, and all PMDA is stirred and polymerized to complete reaction, to obtain a polyamic acid (PAA) solution.
[0039] Preparation of dopamine modified boron nitride nanosheets / polyamic acid (BNNS@PDA / PAA) solution: adding BNNS@PDA powder to PAA solution, stirring and reacting, to obtain BNNS@PDA / PAA solution;
[0040] S2: Preparation of BNNS@PDA / PAA composite fiber felt using BNNS@PDA / PAA solution;
[0041] BNNS@PDA / PAA solution was made into BNNS@PDA / PAA composite fiber felt by electrospinning, specifically, BNNS@PDA / PAA solution was loaded into an injection needle tube equipped with a metal needle, and then the injection needle tube was horizontally fixed on the injection device, the positive electrode of the high-voltage power supply of the electrospinning instrument was connected to the metal needle, tin foil collection paper was wrapped on the roller-shaped negative electrode, the injection needle tube was aligned with the center of the roller, and the working room of the electrospinning instrument was kept in a sealed state. During the electrospinning process, the working room temperature was 18-25°C, the relative humidity of the environment was 50%-60%, the voltage of the high-voltage power supply was 15-25kV, the distance from the needle to the center of the roller was 15-20cm, and the roller speed was 40-120m / min.
[0042] S3: Treat the BNNS@PDA / PAA composite fiber felt under vacuum; the vacuum treatment conditions are: vacuum degree 0.08-0.1MPa, temperature 60-80°C, time 4-6h. After treatment, the BNNS@PDA / PAA composite fiber felt is thermally imidized at a stepwise temperature, cooled to room temperature and taken out to obtain a dopamine-modified boron nitride nanosheet / polyimide (BNNS@PDA / PI) thermally conductive insulating composite fiber felt;
[0043] S4: Compression molding several layers of BNNS@PDA / PI thermal conductive composite fiber felt to obtain BNNS@PDA / PI thermal conductive insulating composite film. The specific process of compression molding is: weigh 2g of BNNS@PDA / PI thermal conductive composite fiber felt, cut it into a sample with a size of 20mm×20mm, put it into the mold, and compression mold it on a small flat vulcanizer. The compression molding temperature is 290-320℃, the pressure is 5-10MPa, and the time is 10-15min.
[0044] The present invention utilizes dopamine (DA) to oxidize and self-polymerize under the weak base condition formed by tris(hydroxymethyl)aminomethane to form polydopamine (PDA) with strong adhesion, and uses PDA to perform surface modification on boron nitride nanosheets (BNNS) to obtain polydopamine-modified boron nitride nanosheets (BNNS@PDA) with a large number of active groups (-NH and -OH), and simultaneously performs surface activation modification on the inorganic filler BNNS, effectively improving the dispersibility of BNNS, increasing the contact area between thermal conductive fillers and thermal conductive fillers, and between thermal conductive fillers and fibers, reducing the interface defects and heat transfer resistance between the matrix and the filler, reducing the scattering of phonons during the diffusion process, and thus improving the thermal conductivity of the composite material. Using BNNS@PDA as filler and polyimide (PI) fiber as matrix, a polydopamine-modified boron nitride nanosheet / polyimide (BNNS@PDA / PI) composite film is prepared, effectively improving the thermal conductivity of the polyimide neutron shielding film, effectively extending the service life of the film, and ensuring the reliability of the equipment.
[0045] The present invention adopts a method combining in-situ polymerization, electrostatic spinning and compression molding to achieve uniform dispersion and directional arrangement of BNNS@PDA inside the PI matrix, so that the thermal conductivity λ of the BNNS@PDA / PI thermal conductive insulation composite material is significantly improved, while maintaining good breakdown strength. Among them, BNNS accounts for 5% to 40% of the mass of PAA, and the addition amount of PDA is 20%-40% of the mass of BNNS. The thermal conductivity λ of the material is increased from 0.048W / mK in the prior art to 0.23W / mK to 1.75W / mK; the breakdown strength is between 11.8 and 16.4kV / mm.
[0046] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0047] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0048] Comparative Example 1
[0049] Add 1.08 g of ODA into a three-necked flask, add 19 g of DMF under ice-water bath conditions, stir until ODA is completely dissolved, then add 1.244 g of PMDA in batches, 0.15 g of PMDA in each batch, and after all PMDA is added and dissolved, mechanically stir for 30 min, then add 0.19 g of BNNS, continue stirring for 30 min, and polycondense to obtain BNNS / PAA solution.
[0050] The BNNS / PAA solution was loaded into a 6 mL injection syringe equipped with a metal needle, and then the injection syringe was fixed horizontally on the injection device, the positive electrode connector of the high-voltage power supply of the electrospinning instrument was connected to the metal needle, the tin foil collection paper was wrapped on the roller-shaped negative electrode, the injection syringe was aligned with the center of the roller, the studio of the electrospinning instrument was kept sealed, and the studio temperature was kept at 18°C, the electrostatic positive voltage was 15kV, the working distance was 15cm, the relative humidity of the environment was 50%, and the receiving shaft speed was 40m / min. The BNNS / PAA thermal conductive composite fiber felt was obtained by electrospinning, and after removing the solvent at 60°C in a vacuum oven for 4h, thermal imidization was carried out according to the program of 120°C / 1h+200°C / 1h+250°C / 1h, and the heating rate was 5°C / min. After cooling to room temperature, it was taken out to obtain the BNNS / PI thermal conductive composite fiber felt;
[0051] 2 g of BNNS / PI thermal conductive composite fiber felt was cut into 20 mm × 20 mm samples and loaded into a mold. BNNS / PI composite materials were prepared by compression molding on a small flat vulcanizer at a molding temperature of 290 ° C, a pressure of 5 MPa, and a molding time of 10 min to obtain a BNNS / PI composite film, in which BNNS accounted for 5% of the mass of PAA.
[0052] Comparative Example 2
[0053] Add 1.2 g of ODA into a three-necked flask, add 20 g of DMF under ice-water bath conditions, and after ODA is completely dissolved, add 1.36 g of PMDA in batches, with 0.15 g of PMDA added in each batch. After all PMDA is added and dissolved, add 0.38 g of BNNS after mechanical stirring for 30 min, and continue stirring for 30 min to obtain BNNS / PAA solution by condensation.
[0054] The BNNS / PAA solution was loaded into a 6 mL injection syringe equipped with a metal needle, and then the injection syringe was fixed horizontally on the injection device, the positive electrode connector of the high-voltage power supply of the electrospinning instrument was connected to the metal needle, tin foil collection paper was wrapped on the roller-shaped negative electrode, the injection syringe was aligned with the center of the roller, the working room of the electrospinning instrument was kept sealed, and the working room temperature was kept at 18°C, the electrostatic positive voltage was 20 kV, the working distance was 15 cm, the relative humidity of the environment was 50%, the receiving shaft speed was 120 m / min, and the BNNS / PAA thermal conductive composite fiber felt was obtained by electrospinning. After removing the solvent at 60°C in a vacuum oven for 4 h, thermal imidization was carried out according to the program of 120°C / 1h+200°C / 1h+250°C / 1h, with a heating rate of 5°C / min. After cooling to room temperature, it was taken out to obtain the BNNS / PI thermal conductive composite fiber felt.
[0055] 2g of BNNS / PI thermal conductive composite fiber felt was cut into 20mm×20mm samples and loaded into a mold. BNNS / PI thermal conductive insulating composite material was prepared by compression molding on a small flat vulcanizer. The molding temperature was 320℃, the pressure was 10MPa, and the molding time was 10min. The prepared BNNS / PI composite film contained 10% of the mass of PAA in which BNNS accounted for.
[0056] Example 1
[0057] 1.2 g of Tris solid powder was added to a mixed solution of 300 mL of deionized water and 100 mL of ethanol and mixed evenly; 2.0 g of BNNS was added and ultrasonically dispersed for 10 min. After stirring, the mixture was evenly dispersed. 0.8 g of dopamine powder was added and stirred at room temperature for 6 h until the solution turned gray-black. The mixture was allowed to stand at room temperature for 24 h, the supernatant was removed, and the mixture was dried at 60 °C for 12 h to obtain BNNS@PDA.
[0058] 1.08 g of ODA was added into a three-necked flask, and 19 g of DMF was added under ice-water bath conditions. After ODA was completely dissolved, 1.244 g of PMDA was added in batches, with 0.15 g of PMDA added in each batch. After all PMDA was added and dissolved, 0.19 g of BNNS@PDA was added after mechanical stirring for 30 min, and stirring was continued for 30 min to obtain BNNS@PDA / PAA solution by condensation.
[0059] The BNNS@PDA / PAA solution was loaded into a 6 mL injection needle tube equipped with a metal needle, and then the injection needle tube was fixed horizontally on the injection device, the positive electrode connector of the high-voltage power supply of the electrospinning instrument was connected to the metal needle, the tin foil collection paper was wrapped on the roller-shaped negative electrode, the injection needle tube was aligned with the center of the roller, the studio of the electrospinning instrument was kept sealed, and the studio temperature was kept at 18°C, the electrostatic positive voltage was 18kV, the working distance was 15cm, the relative humidity of the environment was 50%, and the receiving shaft speed was 120m / min. The BNNS@PDA / PAA thermal conductive composite fiber felt was obtained by electrospinning, and after removing the solvent at 60°C in a vacuum oven for 4h, thermal imidization was carried out according to the program of 120°C / 1h+200°C / 1h+250°C / 1h, and the heating rate was 5°C / min. After cooling to room temperature, it was taken out to obtain the BNNS@PDA / PI thermal conductive composite fiber felt;
[0060] 2g of BNNS@PDA / PI thermal conductive composite fiber felt was cut into 20mm×20mm samples and loaded into a mold. BNNS@PDA / PI thermal conductive insulating composite material was prepared by compression molding on a small flat vulcanizer. The molding temperature was 320℃, the pressure was 10MPa, and the molding time was 10min. The prepared BNNS@PDA / PI composite film contained 5% of the mass of PAA and the amount of PDA added was 40% of the mass of BNNS.
[0061] Example 2
[0062] 1.2 g of Tris solid powder was added to a mixed solution of 300 mL of deionized water and 100 mL of ethanol and mixed evenly; 2.0 g of BNNS was added and ultrasonically dispersed for 10 min to make it evenly dispersed, 0.8 g of dopamine powder was added and stirred at room temperature for 6 h until the solution turned gray-black; the solution was allowed to stand at room temperature for 24 h, the supernatant was removed, and the dopamine-modified boron nitride nanosheets were dried at 60 ° C for 12 h.
[0063] 1.08 g of ODA was added to a three-necked flask, and 19 g of DMF was added under ice-water bath conditions. After the ODA was completely dissolved, 1.244 g of PMDA was added in batches, with 0.15 g of PMDA added in each batch. After all PMDA was added and dissolved, 0.38 g of BNNS@PDA was added after mechanical stirring for 30 min, and stirring was continued for 30 min to obtain BNNS@PDA / PAA solution by condensation.
[0064] The BNNS@PDA / PAA solution was loaded into a 6 mL syringe equipped with a metal needle, and then the syringe was fixed horizontally on the injection device, the positive electrode connector of the high-voltage power supply of the electrospinning instrument was connected to the metal needle, the tin foil collection paper was wrapped on the roller-shaped negative electrode, the syringe was aligned with the center of the roller, the studio of the electrospinning instrument was kept sealed, and the studio temperature was kept at 18°C, the electrostatic positive voltage was 20 kV, the working distance was 15 cm, the relative humidity of the environment was 50%, and the receiving shaft speed was 120 m / min. The BNNS@PDA / PAA thermal conductive composite fiber felt was obtained by electrospinning, and the solvent was removed in a vacuum oven at 60°C After 4 hours, thermal imidization was carried out according to the program of 120℃ / 1h+200℃ / 1h+250℃ / 1h, with a heating rate of 5℃ / min, and the mixture was taken out after cooling to room temperature to obtain BNNS@PDA / PI thermal conductive composite fiber felt; 2g of BNNS@PDA / PI thermal conductive composite fiber felt was cut into 20mm×20mm samples and loaded into a mold, and molded on a small flat vulcanizer to prepare BNNS@PDA / PI thermal conductive insulation composite material, with a molding temperature of 320℃, a pressure of 10MPa, and a molding time of 10min to prepare BNNS@PDA / PI composite film, in which BNNS accounted for 10% of the mass of PAA. , and the amount of PDA added was 40% of the mass of BNNS.
[0065] Example 3
[0066] 1.2 g of tris(hydroxymethyl)aminomethane) solid powder was added to a mixed solution of 300 mL of deionized water and 100 mL of ethanol and mixed evenly; 2.0 g of BNNS was added and ultrasonically dispersed for 10 min to make it evenly dispersed; 0.8 g of dopamine powder was added and stirred at room temperature for 6 h until the solution turned gray-black; the solution was allowed to stand at room temperature for 24 h, the supernatant was removed, and the solution was dried at 60 ° C for 12 h to prepare polydopamine-modified boron nitride nanosheets.
[0067] 1.08 g of ODA was added into a three-necked flask, and 19 g of DMF was added in an ice-water bath. After the ODA was completely dissolved, 1.244 g of PMDA was added in batches, with 0.15 g of PMDA added in each batch. After all PMDA was added and dissolved, 0.76 g of BNNS@PDA was added after mechanical stirring for 30 min, and stirring was continued for 30 min to obtain BNNS@PDA / PAA solution by condensation.
[0068] The BNNS@PDA / PAA solution was loaded into a 6 mL injection syringe equipped with a metal needle, and then the injection syringe was fixed horizontally on the injection device, the positive electrode connector of the high-voltage power supply of the electrospinning instrument was connected to the metal needle, the tin foil collection paper was wrapped on the roller-shaped negative electrode, the injection syringe was aligned with the center of the roller, the studio of the electrospinning instrument was kept sealed, and the studio temperature was kept at 18°C, the electrostatic positive voltage was 20 kV, the working distance was 15 cm, the relative humidity of the environment was 50%, and the receiving shaft speed was 80 m / min. BNNS@PDA / PAA thermal conductive composite fiber felt was obtained by electrospinning, and after removing the solvent at 60°C in a vacuum oven for 4 h, thermal imidization was carried out according to the procedure of 120°C / 1h+200°C / 1h+250°C / 1h, with a heating rate of 5°C / min, and it was taken out after cooling to room temperature to obtain BNNS@PDA / PI thermal conductive composite fiber felt; 2 g The BNNS@PDA / PI thermal conductive composite fiber felt was cut into 20mm×20mm samples and loaded into a mold. The BNNS@PDA / PI thermal conductive insulating composite material was prepared by compression molding on a small flat vulcanizer at a molding temperature of 300°C, a pressure of 5MPa, and a molding time of 10min. The BNNS@PDA / PI composite film was prepared, in which BNNS accounted for 30% of the mass of PAA. The amount of PDA added was 40% of the mass of BNNS.
[0069] Example 4
[0070] 1.2 g of tris(hydroxymethyl)aminomethane) solid powder was added to a mixed solution of 300 mL of deionized water and 100 mL of ethanol and mixed evenly; 2.0 g of BNNS was added and ultrasonically dispersed for 10 min to make it evenly dispersed; 0.8 g of dopamine powder was added and stirred at room temperature for 6 h until the solution turned gray-black; the solution was allowed to stand at room temperature for 24 h, the supernatant was removed, and the polydopamine-modified boron nitride nanosheets were dried at 60 °C for 12 h.
[0071] 1.08 g of ODA was added into a three-necked flask, and 19 g of DMF was added in an ice-water bath. After the ODA was completely dissolved, 1.244 g of PMDA was added in batches, with 0.15 g of PMDA added in each batch. After all PMDA was added and dissolved, 1.14 g of BNNS@PDA was added after mechanical stirring for 30 min, and stirring was continued for 30 min to obtain BNNS@PDA / PAA solution by condensation.
[0072] The BNNS@PDA / PAA solution was loaded into a 6 mL syringe equipped with a metal needle, and then the syringe was fixed horizontally on the injection device, the positive electrode connector of the high-voltage power supply of the electrospinning instrument was connected to the metal needle, the tin foil collection paper was wrapped on the roller-shaped negative electrode, the syringe was aligned with the center of the roller, the studio of the electrospinning instrument was kept sealed, and the studio temperature was kept at 18°C, the electrostatic positive voltage was 20 kV, the working distance was 15 cm, the relative humidity of the environment was 50%, and the receiving shaft speed was 120 m / min. The BNNS@PDA / PAA thermal conductive composite fiber felt was obtained by electrospinning, and the solvent was removed in a vacuum oven at 60°C After 4 hours, thermal imidization was carried out according to the procedure of 120℃ / 1h+200℃ / 1h+250℃ / 1h, with a heating rate of 5℃ / min, and the mixture was taken out after cooling to room temperature to obtain BNNS@PDA / PI thermal conductive composite fiber felt; 2g of BNNS@PDA / PI thermal conductive composite fiber felt was cut into 20mm×20mm samples and loaded into a mold, and molded on a small flat vulcanizer to prepare BNNS@PDA / PI thermal conductive insulation composite material, with a molding temperature of 320℃, a pressure of 10MPa, and a molding time of 10min to prepare BNNS@PDA / PI composite film, in which BNNS accounted for 20% of the mass of PAA. , and the addition amount of PDA accounted for 40% of the mass of BNNS.
[0073] The thermal conductivity λ of the BNNS / PI composite films prepared in Comparative Examples 1 and 2 of the present invention is shown in Figure 3 , breakdown strength see Figure 4 .
[0074] The thermal conductivity λ of the BNNS@PDA / PI composite films prepared in Examples 1 to 4 is shown in Figure 2 as well as Figure 3 , breakdown strength see Figure 4 .
[0075] Depend on Figure 2 , 3 It can be seen that after BNNS and PI are compounded, the thermal conductivity of the film is significantly improved.
[0076] Depend on Figure 4 It can be seen that as the BNNS content gradually increases, the compressive strength of the composite film decreases. When the BN mass fraction reaches 10%, the compressive strength of the BN / PI composite film is 7.8 kV / mm, which is 52.56% lower than that of the BNNS@PDA / PI film (11.9 kV / mm). It can be seen that the modification of PDA is beneficial to retaining the compressive strength of the PI film itself due to the strong viscosity of PDA.
[0077] Example 5
[0078] A method for preparing a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film comprises the following steps:
[0079] S1: Preparation of polydopamine modified boron nitride nanosheets (BNNS@PDA): Tris was added to a mixed solution of deionized water and ethanol in a volume ratio of 3:1, stirred to fully dissolve Tris, added BNNS, and dispersed evenly after ultrasound, stirred to disperse BNNS evenly, and ultrasound could also be used to assist in dispersing BNNS evenly. Then DA was added and stirred until the reaction was complete. At this time, the solution was gray-black. After standing at room temperature, the supernatant was removed, and the precipitated product was dried at 60°C for 12 hours to obtain BNNS@PDA.
[0080] Preparation of polyamic acid (PAA) solution: Add 1.08 g of ODA into a three-necked flask, add 19 g of DMF under ice-water bath conditions, and after ODA is completely dissolved, add 1.244 g of PMDA in batches, with 0.15 g of PMDA added in each batch. After all PMDA is added and dissolved, mechanically stir for 30 minutes to complete the polymerization reaction to obtain a PAA solution.
[0081] Preparation of dopamine modified boron nitride nanosheets / polyamic acid (BNNS@PDA / PAA) solution: BNNS@PDA powder was added to PAA solution, stirred for reaction, and BNNS@PDA / PAA solution was obtained, wherein BNNS accounted for 5% of the mass of PAA and the amount of PDA added was 20% of the mass of BNNS.
[0082] S2: The BNNS@PDA / PAA solution was made into a BNNS@PDA / PAA composite fiber felt by the electrospinning method. Specifically, the BNNS@PDA / PAA solution was loaded into an injection syringe equipped with a metal needle, and then the injection syringe was horizontally fixed on the injection device. The positive electrode of the high-voltage power supply of the electrospinning apparatus was connected to the metal needle, and tin foil collection paper was wrapped on the roller-shaped negative electrode. The injection syringe was aligned with the center of the roller, and the working room of the electrospinning apparatus was kept sealed. During the electrospinning process, the working room temperature was 18°C, the relative humidity was 50%, the high-voltage power supply voltage was 15kV, the distance from the needle to the center of the roller was 15cm, and the roller speed was 40m / min.
[0083] S3: Treat the BNNS@PDA / PAA composite fiber felt under vacuum; the vacuum treatment conditions are: vacuum degree 0.08MPa, temperature 60℃, time 4h. After treatment, thermal imidization is carried out according to the program of 120℃ / 1h+200℃ / 1h+250℃ / 1h, and the heating rate is 5℃ / min. After cooling to room temperature, take out to obtain BNNS@PDA / PI thermally conductive insulating composite fiber felt;
[0084] S4: The three layers of BNNS@PDA / PI thermal conductive composite fiber felt were molded to obtain a BNNS@PDA / PI thermal conductive insulating composite film. The specific process of the molding is as follows: 2g of BNNS@PDA / PI thermal conductive composite fiber felt was weighed, cut into samples of 20mm×20mm in size and placed in a mold, and molded on a small flat vulcanizer at a temperature of 290°C, a pressure of 5MPa, and a time of 10min.
[0085] The thermal conductivity λ of the material prepared in this embodiment is 0.23 W / mK, and the breakdown strength is 11.8 kV / mm.
[0086] Example 6
[0087] A method for preparing a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film comprises the following steps:
[0088] S1: Preparation of polydopamine modified boron nitride nanosheets (BNNS@PDA): Tris was added to a mixed solution of deionized water and ethanol in a volume ratio of 3:1, stirred to fully dissolve Tris, added BNNS, and dispersed evenly after ultrasound, stirred to disperse BNNS evenly, and ultrasound could also be used to assist in dispersing BNNS evenly. Then DA was added and stirred until the reaction was complete. At this time, the solution was gray-black. After standing at room temperature, the supernatant was removed, and the precipitated product was dried at 80°C for 24 hours to obtain BNNS@PDA.
[0089] Preparation of polyamic acid (PAA) solution: Add 1.08 g of ODA into a three-necked flask, add 19 g of DMF under ice-water bath conditions, and after ODA is completely dissolved, add 1.244 g of PMDA in batches, with 0.15 g of PMDA added in each batch. After all PMDA is added and dissolved, mechanically stir for 30 minutes to complete the polymerization reaction to obtain a PAA solution.
[0090] Preparation of dopamine modified boron nitride nanosheets / polyamic acid (BNNS@PDA / PAA) solution: BNNS@PDA powder was added to PAA solution, stirred for reaction, and BNNS@PDA / PAA solution was obtained, wherein BNNS accounted for 20% of the mass of PAA and the amount of PDA added was 25% of the mass of BNNS.
[0091] S2: The BNNS@PDA / PAA solution was made into a BNNS@PDA / PAA composite fiber felt by the electrospinning method, specifically: the BNNS@PDA / PAA solution was loaded into an injection syringe equipped with a metal needle, and then the injection syringe was horizontally fixed on the injection device, the positive electrode of the high-voltage power supply of the electrospinning instrument was connected to the metal needle, tin foil collection paper was wrapped on the roller-shaped negative electrode, the injection syringe was aligned with the center of the roller, and the working room of the electrospinning instrument was kept in a sealed state. During the electrospinning process, the working room temperature was 18°C, the relative humidity of the environment was 60%, the high-voltage power supply voltage was 20kV, the distance from the needle to the center of the roller was 20cm, and the roller speed was 60m / min.
[0092] S3: Treat the BNNS@PDA / PAA composite fiber felt under vacuum; the vacuum treatment conditions are: vacuum degree 0.09MPa, temperature 70℃, time 5h. After treatment, thermal imidization is carried out according to the program of 120℃ / 1h+200℃ / 1h+250℃ / 1h, and the heating rate is 5℃ / min. After cooling to room temperature, take out to obtain BNNS@PDA / PI thermally conductive insulating composite fiber felt;
[0093] S4: Four layers of BNNS@PDA / PI thermal conductive composite fiber felt were molded to obtain BNNS@PDA / PI thermal conductive insulating composite film. The specific process of molding is as follows: 2g of BNNS@PDA / PI thermal conductive composite fiber felt was weighed, cut into samples of 20mm×20mm in size and placed in a mold, and molded on a small flat vulcanizer at a temperature of 300°C, a pressure of 8MPa, and a time of 12min.
[0094] The thermal conductivity λ of the material prepared in this embodiment is 0.55 W / mK, and the breakdown strength is 14.8 kV / mm.
[0095] Example 7
[0096] A method for preparing a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film comprises the following steps:
[0097] (1) Adding BNNS@PDA powder to PAA solution and stirring the mixture to obtain BNNS@PDA / PAA solution, wherein BNNS accounts for 25% of the mass of PAA and the amount of PDA added is 29% of the mass of BNNS;
[0098] (2) The electrospinning chamber is kept sealed, the temperature of the electrospinning chamber is 24°C, the relative humidity is 60%, the voltage of the high voltage power supply is 25 kV, the distance from the needle to the center of the roller is 20 cm, and the roller speed is 100 m / min. The BNNS@PDA / PAA solution is made into a BNNS@PDA / PAA composite fiber felt by electrospinning;
[0099] (3) The BNNS@PDA / PAA composite fiber felt was treated at a vacuum degree of 0.09 MPa and a temperature of 70°C for 6 h, and then thermal imidization was performed at a rate of 120°C / 1h+200°C / 1h+250°C / 1h with a heating rate of 5°C / min. After cooling to room temperature, the felt was taken out to obtain a BNNS@PDA / PI thermally conductive insulating composite fiber felt.
[0100] (4) Two layers of BNNS@PDA / PI thermal conductive composite fiber felt were compression molded to obtain a BNNS@PDA / PI thermal conductive insulating composite film. The compression molding temperature was 320°C, the pressure was 10 MPa, and the time was 15 min.
[0101] The thermal conductivity λ of the material prepared in this embodiment is 0.75 W / mK, and the breakdown strength is 15.8 kV / mm.
[0102] Example 8
[0103] A method for preparing a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film comprises the following steps:
[0104] (1) Adding BNNS@PDA powder to PAA solution and stirring to react, a BNNS@PDA / PAA solution was prepared, wherein the BNNS accounted for 30% of the mass of PAA and the amount of PDA added was 35% of the mass of BNNS;
[0105] (2) The working room of the electrospinning apparatus is kept sealed, the temperature of the electrospinning working room is 25°C, the relative humidity of the environment is 60%, the voltage of the high voltage power supply is 25 kV, the distance from the needle to the center of the roller is 20 cm, and the roller speed is 120 m / min. The BNNS@PDA / PAA solution is made into a BNNS@PDA / PAA composite fiber felt by an electrospinning method;
[0106] (3) The BNNS@PDA / PAA composite fiber felt was treated at a vacuum degree of 0.1 MPa and a temperature of 80°C for 6 h, and then thermal imidization was performed at a temperature of 120°C / 1h+200°C / 1h+250°C / 1h with a heating rate of 5°C / min. After cooling to room temperature, the felt was taken out to obtain a BNNS@PDA / PI thermally conductive insulating composite fiber felt.
[0107] (4) Two layers of BNNS@PDA / PI thermal conductive composite fiber felt were compression molded to obtain a BNNS@PDA / PI thermal conductive insulating composite film. The compression molding temperature was 320°C, the pressure was 10 MPa, and the time was 15 min.
[0108] The thermal conductivity λ of the material prepared in this embodiment is 1.0 W / mK, and the breakdown strength is 16.8 kV / mm.
[0109] Example 9
[0110] A method for preparing a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film comprises the following steps:
[0111] (1) Adding BNNS@PDA powder to PAA solution and stirring the mixture to obtain BNNS@PDA / PAA solution, wherein BNNS accounts for 40% of the mass of PAA and the amount of PDA added is 37% of the mass of BNNS;
[0112] (2) The working room of the electrospinning apparatus is kept sealed, the temperature of the electrospinning working room is 25°C, the relative humidity of the environment is 60%, the voltage of the high voltage power supply is 25 kV, the distance from the needle to the center of the roller is 20 cm, and the roller speed is 100 m / min. The BNNS@PDA / PAA solution is made into a BNNS@PDA / PAA composite fiber felt by an electrospinning method;
[0113] (3) The BNNS@PDA / PAA composite fiber felt was treated at a vacuum degree of 0.1 MPa and a temperature of 70°C for 6 h, and then thermal imidization was performed at a temperature of 120°C / 1h+200°C / 1h+250°C / 1h with a heating rate of 5°C / min. After cooling to room temperature, the felt was taken out to obtain a BNNS@PDA / PI thermally conductive insulating composite fiber felt.
[0114] (4) Two layers of BNNS@PDA / PI thermal conductive composite fiber felt were compression molded to obtain a BNNS@PDA / PI thermal conductive insulating composite film. The compression molding temperature was 320°C, the pressure was 10 MPa, and the time was 15 min.
[0115] The thermal conductivity λ of the material prepared in this embodiment is 1.55 W / mK, and the breakdown strength is 16.0 kV / mm.
[0116] Example 10
[0117] A method for preparing a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film comprises the following steps:
[0118] (1) Adding BNNS@PDA powder to PAA solution and stirring to react, a BNNS@PDA / PAA solution was prepared, wherein the BNNS accounted for 40% of the mass of PAA and the amount of PDA added was 40% of the mass of BNNS;
[0119] (2) The electrospinning chamber is kept sealed, the temperature of the electrospinning chamber is 24°C, the relative humidity is 60%, the voltage of the high voltage power supply is 25 kV, the distance from the needle to the center of the roller is 20 cm, and the roller speed is 100 m / min. The BNNS@PDA / PAA solution is made into a BNNS@PDA / PAA composite fiber felt by electrospinning;
[0120] (3) The BNNS@PDA / PAA composite fiber felt was treated at a vacuum degree of 0.09 MPa and a temperature of 70°C for 6 h, and then thermal imidization was performed at a rate of 120°C / 1h+200°C / 1h+250°C / 1h with a heating rate of 5°C / min. After cooling to room temperature, the felt was taken out to obtain a BNNS@PDA / PI thermally conductive insulating composite fiber felt.
[0121] (4) Two layers of BNNS@PDA / PI thermal conductive composite fiber felt were compression molded to obtain a BNNS@PDA / PI thermal conductive insulating composite film. The compression molding temperature was 320°C, the pressure was 10 MPa, and the time was 15 min.
[0122] The thermal conductivity λ of the material prepared in this embodiment is 1.75 W / mK, and the breakdown strength is 16.5 kV / mm.
[0123] The present invention also protects the application of the polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film prepared according to the above method in the field of electronic packaging. The film has good insulation performance and thermal conductivity, and the service life of the film is effectively extended, ensuring the reliability of the device and equipment.
[0124] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film, characterized in that: The following steps are involved: S1: adding polydopamine-modified boron nitride nanosheets into a polyamic acid solution, stirring and reacting, to obtain a polydopamine-modified boron nitride nanosheet / polyamic acid solution; The synthesis process of the polydopamine-modified boron nitride nanosheets is specifically as follows: adding tris(hydroxymethyl)aminomethane to a mixed solution of deionized water and ethanol, stirring to fully dissolve the tris(hydroxymethyl)aminomethane, adding boron nitride nanosheets, stirring to evenly disperse the boron nitride nanosheets, then adding dopamine, stirring until the reaction is complete, and obtaining the polydopamine-modified boron nitride nanosheets; Before adding the polydopamine-modified boron nitride nanosheets to the polyamic acid solution, the prepared polydopamine-modified boron nitride nanosheets are dried at 60-80° C. for 12-24 hours to obtain polydopamine-modified boron nitride nanosheet powders, and the polydopamine-modified boron nitride nanosheet powders are added to the polyamic acid solution; S2: preparing a polydopamine-modified boron nitride nanosheet / polyamic acid composite fiber felt using the polydopamine-modified boron nitride nanosheet / polyamic acid solution; S3: subjecting the polydopamine-modified boron nitride nanosheet / polyamic acid composite fiber felt to thermal imidization treatment to obtain a polydopamine-modified boron nitride nanosheet / polyimide thermally conductive composite fiber felt; S4: molding several layers of the polydopamine modified boron nitride nanosheets / polyimide thermal conductive composite fiber felt to obtain the polydopamine modified boron nitride nanosheets / polyimide thermal conductive insulating composite film; In step S1, the added amount of dopamine is 20%-40% of the mass of the boron nitride nanosheets; the boron nitride nanosheets account for 5-40% of the mass of the polyamic acid.
2. The method for preparing a polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film according to claim 1, characterized in that: The synthesis process of the polyamic acid solution is specifically as follows: under ice-water bath conditions, 4,4'-diaminodiphenyl ether is added to N,N-dimethylformamide solution, stirred to completely dissolve 4,4'-diaminodiphenyl ether, and pyromellitic anhydride is added, and stirred continuously until the polymerization reaction is complete to obtain a polyamic acid solution.
3. The method for preparing a polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film according to claim 2, characterized in that: During the synthesis of the polyamic acid solution, pyromellitic anhydride is added in several batches; after each addition of pyromellitic anhydride, it is stirred to dissolve and react completely before adding the next batch of pyromellitic anhydride; the weight of each batch of pyromellitic anhydride added does not exceed 0.2 g.
4. The method for preparing a polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film according to claim 1, characterized in that: In the step S2, the polydopamine-modified boron nitride nanosheet / polyamic acid solution is made into a polydopamine-modified boron nitride nanosheet / polyamic acid composite fiber felt by an electrospinning method; the voltage of the high-voltage power supply during the electrospinning process is 15 kV to 25 kV.
5. The method for preparing a polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film according to claim 1, characterized in that: Before subjecting the polydopamine-modified boron nitride nanosheets / polyamic acid composite fiber felt to thermal imidization, the polydopamine-modified boron nitride nanosheets / polyamic acid composite fiber felt is treated under vacuum; the vacuum treatment conditions are: vacuum degree 0.08-0.1 MPa, temperature 60-80° C., and time 4-6 hours.
6. The method for preparing a polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film according to claim 1, characterized in that: The compression molding process is performed at a temperature of 290-320° C., a pressure of 5-10 MPa, and a time of 10-15 min.
7. A polydopamine-modified boron nitride nanosheet / polyimide thermally conductive insulating composite film, characterized in that: The polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film is prepared by the method described in any one of claims 1 to 6, and has a thermal conductivity of 0.23 to 1.75 W / mK and a breakdown strength of 11.8 to 16.4 kV / mm.
8. Application of the polydopamine modified boron nitride nanosheet / polyimide thermally conductive insulating composite film prepared by the method according to any one of claims 1 to 6 in the field of electronic packaging.
Citation Information
Patent Citations
Polyimide dielectric heat-conduction composite material and preparation method thereof
CN106480533A
High-thermal-conductivity polydopamine modified boron nitride / polyimide composite material and preparation method thereof
CN110713716A